Case Report Penurunan Tingkat Nyeri Pada Pasien Fraktur Femur Dengan Balut Bidai Di IGD RSUD Tidar Kota Magelang - Rizkiana Kurniasari; Al Afik; Cipto Wahyuning Utama (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Fracture is one of the causes of disability caused by trauma due to an accident. Fractures can be caused by direct trauma, for example a collision or blow that results in a broken bone. Splinting is an action carried out as first aid for musculoskeletal injuries so that the injured body part can rest, avoid shifting of the injured bone and reduce the level of pain. By using a splint, the skeletal muscles that are experiencing spasm will slowly relax, thereby reducing the level of pain and holding parts of the body from shifting and reducing pain. To determine the application of splint therapy to reduce the pain level of femur fracture patients in IGD at RSUD Tidar Magelang. The research method used a case report with the nursing intervention of providing splints on the pain level of fracture patients. Conducted 3 observations every 30 minutes on the patient Mr. M, 27 years old, who was involved in a traffic accident. From the results of the research, a nursing intervention was carried out, namely by providing a splint dressing for 3 observations every 30 minutes. The result was that there was a decrease in the level of pain before and after the splint dressing. Based on research conducted with Mr. Therefore, the reduction in pain levels in femur fracture patients with splint dressing in the emergency room at Tidar Hospital Magelang can be concluded that splint therapy has an effect on the pain level of fracture patients by reducing the level of the pain scale.